Spectroscopic properties and conduction mechanism of KAl(SO4)2:xSm: A multifunctional materials for optical and electrochemical applications. Issue 15 (1st August 2022) - Souemti, Ahmed; Labidi, Islem; Megriche, Adel
Abstract: Anhydrous α-alum materials doped with the trivalent samarium oxide Sm2 O3 and denoted as KAl(SO4 )2 :xSm (x = 0; 0.5; 1; 1.5; 2; 2.5% mol.) are prepared by the solid-state reaction method at 350 °C. The resulting phases are crystallized in a simple hexagonal structure with space group P321. Powder X-ray diffraction (XRD), Infrared (IR), and Raman spectroscopies confirmed a high purity of phases with variation in lattice parameters according to the amount of doping. Optical measurements through absorption and fluorescence spectroscopies in the ultra-violet and visible regions prove the different electronic transitions between excited levels and 6 H5/2 ground state of Sm 3+, the incorporation of samarium in the crystal structure, and suggest the quenching phenomenon. The materials presented in the study showed an ionic semiconductor behavior with an increase in their conductivity as a function of the doping level. A 1D conduction is made according to the Correlated Barrier Hopping CBH model by cations mobility in crystalline sites under the effect of thermal agitation in the [170–250 °C] region. KAl(SO4 )2 : xSm (x = 1.5% mol.) with its lower activation energy value, is suggested as a suitable cathode material for aluminum-based batteries.